Polymorphism of the Beta-1 Gly389Arg receptor in patients with dual atrioventricular nodal physiology - Douglas Joel Boris; Tiago Luiz Luz Leiria; Diego Chemello; Marco Aurélio Lumertz Saffi; Gustavo Glotz de Lima (Indian Pacing and Electrophysiology Journal, 2020)
Introduction: Gly389Arg β1 adrenergic receptor polymorphisms seem to exert an influence on the modulation of the adrenergic effect in several types of patients. This study aimed to determine the prevalence of Gly389Arg polymorphisms among patients with evidence of double nodal pathway and to correlate the electrophysiological properties with the different genotypes of the respective polymorphisms. Methods: A cross-sectional, descriptive and analytical study was designed to assess 49 patients, with evidence of double nodal pathway, submitted to electrophysiological study. Genomic DNA was extracted from peripheral blood leukocytes and the genotypes of the Arg389Gly polymorphisms were identified in all individuals by PCR/RFLP (polymerase chain reaction/restriction fragment length polymorphism). Results: The majority of patients were female and had supraventricular tachycardia (75.5%). The prevalence of Arg389Arg genotype was found in 32 patients (65.3%), Arg389Gly genotype in 16 patients (32.7%) and Gly389Gly genotype in 1 patient (2%). With respect to the induction of nodal reentrant tachycardia, it was possible to induce non-isoproterenol tachycardia in 32 patients (65.3%), of whom 24 had the Arg389Arg genotype and 8 the Arg389Gly and Gly389Gly genotype (p = 0.05). The resting heart rate of patients of the Arg389Arg genotype was 81 ± 18 bpm and the Arg389Gly and Gly389Gly genotype of 71 ± 9 bpm (p = 0.044). Body mass index (BMI) among patients with genotype Arg389Gly and Gly389Gly was 29.8 ± 7.1 and patients with the Arg389Arg genotype was 26.2 ± 4.6 (p = 0.034). Conclusion: The Arg389Arg genotype was more easily related to triggering arrhythmia, higher resting heart rate and lower BMI.